Pharmacotherapy of Autism Spectrum Disorder: Results from the Randomized BAART Clinical Trial. Issue 6 (29th May 2019) - DeVane, C. Lindsay; Charles, Jane M.; Abramson, Ruth K.; Williams, John E.; Carpenter, Laura A.; Raven, Sarah; Gwynette, Frampton; Stuck, Craig A.; Geesey, Mark E.; Bradley, Catherine; Donovan, Jennifer L.; Hall, Alicia G.; et al.
Abstract : The objective of this trial, Biomarkers in Autism of Aripiprazole and Risperidone Treatment (BAART), was to provide support and guidance for an evidence‐based approach for the selection and monitoring of initial pharmacotherapy in patients with autism by assessing predictors of efficacy, tolerability, and safety. This randomized double‐blind parallel‐group study was conducted in three academic medical centers and a single private pediatric practice. Eighty children or adolescents (aged 6–17 yrs) with autistic disorder were enrolled, and 61 patients were randomized to the study drug. Of those patients, 51 completed the 10‐week trial, and 31 completed an optional 12‐week blinded extension phase. All patients were treated with 2 weeks of placebo before random assignment to receive aripiprazole (31 patients) or risperidone (30 patients) for 10 weeks. Sixteen placebo responders (20%) were excluded from further analysis. Drug dosing followed U.S. Food and Drug Administration (FDA) labeling, and weekly dosage adjustments were allowed until week 4; patients were then maintained on a fixed dose for 6 additional weeks. Safety, physical, and psychological assessments were recorded weekly or every 2 weeks. No significant differences in severity of illness between the aripiprazole and risperidone groups were noted at baseline. All patients significantly improved on the Aberrant Behavior Checklist‐Irritability subscale after 1 week and continued for the remaining 9 weeks and the extension phase. Improvement was greatest in the risperidone group at every assessment period and was statistically significantly better than that in the aripiprazole group at weeks 3 and 6 (p<0.05). No dose‐limiting adverse events occurred during the dose‐titration period. Mean weight gain in the aripiprazole group was significantly less than that in the risperidone group at week 4 (0.62 vs 1.38 kg, p=0.033) and week 10 (1.61 vs 3.31 kg, p<0.001), but the difference became nonsignificant for the 31 patients completing the 3‐month extension phase (4.36 vs 5.55 kg, p=0.26). Pharmacotherapy of patients with autism spectrum disorder resulted in behavioral improvement within 1 week and lasted at least 22 weeks. Weight gain occurred to a greater degree with risperidone than aripiprazole initially, but the differences became nonsignificant by the end of the trial. Our trial supports previous results of drug efficacy and safety in patients with autism spectrum disorder from other trials and extends the evidence‐based support for choosing an FDA‐approved drug for initial pharmacotherapy for autism spectrum disorder.